Meteorological Factors and the Spread of COVID‐19: A Territorial Analysis in Italy - Vito Telesca; Gianfranco Castronuovo; Gianfranco Favia; Mariarosaria Marra; Marica Rondinone; Alessandro Ceppi (Meteorological Applications)
ABSTRACT The COVID‐19 pandemic has generated significant global impacts on health and society, imposing a comprehensive analysis of its influencing factors, including weather variables. This study investigates the interaction between meteorological conditions and the spread of COVID‐19 in three Italian regions: Lombardia, Emilia‐Romagna, and Puglia. Effects of weather variables, such as air temperature, relative humidity, dew point, solar radiation, wind speed, and barometric pressure, are explored in the incidence of disease. Observed meteorological and health data are taken from various sources, such as the citizen‐science Meteonetwork Association and the National Department of Civil Protection, respectively, and they are analyzed with statistical methods and machine learning algorithms. The study emphasizes the necessity of carefully considering key meteorological quantities as primary drivers in illness diffusion and prevention strategies, offering valuable insights to address challenges to the pandemic and ensure the safety of global communities. The results reveal a significant correlation between specific atmospheric variables and the spread of COVID‐19, with dew point temperature as the most influential parameter at low air temperature values.